Study of some factors associated with polyclonal antibody production in rabbit - Lungu, Bianca; Georgescu, Ovidiu; Tudor, Beatrice; Buzan, Roxana; Grijincu, Manuela; Cotarca, Monica; Panaitescu, Carmen; Chen, Kuan-Wei; Torda, Iuliu; Mircu, Calin; et al. (Eximia, 2022)
Obtaining polyclonal antibody (pAbs) is a well-known and the most used procedure is rabbit models. The study was carried out over a period of 2 ½ years for several antigens in White New Zeeland rabbits (regularly two animals for each inoculated antigen). The control variables of antibody production were antibodies’ optical densities measured after inoculation of antigens in animals - both male and female, both young and mature rabbits in the same 59-day standard polyclonal antibody production schedule. In this study, the ages at starting the production did not have a significant impact on optical densities (OD) of pAbs with two exceptions: after the first (2.1726±0.1626 vs. 2.7850±0.3391 at p=0.003) and second immunization (2.1198±0.1266 vs. 2.9778±0.5301, p=0.001) both at 103 dilutions. In the first immunisation, a significant difference was found for 106 dilutions between females and males (mean OD was 0.1182±0.0577 in female vs. 0.1975±0.0885 in male, p=0.035). Additionally, the final body weight was significantly different between males and females (3,864±364 in female vs. 3,507±491 in male, p=0.037). In overall, polyclonal antibody production has an impact on final body weight, total gain, average daily gain and feed conversion depending on the antigen type (protocol) but the level of impact is tolerable for the animals.